ANALISIS IMPLEMENTASI ASPEK PENGENDALIAN OPERASIONAL BERDASARKAN OHSAS 18001 : 2007 DAN PP NO. 50 TAHUN 2012 DI AREA FILLING SHED PT. X - Ratna Yasinta Ayu Maulidha; Hanifa Maher Denny; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
According to International Labor Organization (ILO), there are 20 of 100.000 Indonesian death bacause of work related accident. It happened because Occupational Safety and Health (OSH) programs does not work well. So, Occupational Safety and Health Management System is needed to control OSH program. In Indonesia OSH management system is reguated on Govermental Rule Number 50 in 2012 and every company has to implement this regulation. PT. X apllies OHSAS 18001 : 2007 as their reference on applying OSH management system. The purpose of this research to analyze the implementation of Operating Control based on OHSAS 18001 : 2007 and Govermental Rule Number 50 in 2012. The subjects of this research are 2 people as the key informants and 2 people as the triangulation informants. The results showed that PT. X has been fullfiled all elements on Operation Control of OHSAS 18001 : 2007, and for Govermental Rule Number 50 in 2012, there was some elements had not been fulfilled as the criteria, such us Purchasing, Personal Protective Equipment, Safety Sign, and Lock Out System. PT X need to certify and apply the Occupational Safety and Health Management System based on Govermental Rule Number 50 in 2012 to know the OSH management system implementation level based on Govermental Rule Number 50 in 2012 and to do the duty and for better implementation of OSH management system.